The Solid Grounds Coffee Company (Supper Club novel, 3,, 2020)
"Analyn Sanchez can handle the long hours and arrogant clients that come with her job as a crisis management associate at Denver's largest publicity firm. The high-powered job, expensive condo, and designer wardrobe are all part of her plan to prove to her family that her life choices haven't been in vain. But when she's asked to cover up a client's misdeeds with serious moral and legal ramifications, she can no longer sacrifice her conscience for her career . . . and the cost is no less than her job. Ever since a devastating climbing accident in Central America eight months ago, and a bad decision that dried up his sponsorships, professional rock climber Bryan Shaw has found himself at similar loose ends. When the opportunity to buy a coffee farm in Colombia arises, he jumps on it--only to discover his wandering ways have left him utterly unprepared to run a business. When Bryan returns home and offers Ana a role in his company as a solution to both their problems, she's desperate enough to consider working with the far-too-flippant and far-too-handsome climber, even though he's the polar opposite of her type A nature. As they delve deeper into the business, however, she begins to suspect there's much more to Bryan than she's given him credit for . . . and that sometimes the best plans are the ones you never see coming"--

The Saturday night supper club (The Saturday Night Supper Club, ,, 2018)
Denver chef Rachel Bishop won a James Beard Award and heads up her own fine-dining restaurant-- until she is the target of a smear campaign. Alex Kanin was highlighting the pitfalls of online criticism-- and destroyed the career of a perfect stranger. Plagued by guilt, he agrees to help rebuild Rachel's tarnished image by offering his connections and his home to host an exclusive pop-up dinner party targeted to the Saturday Night Supper Club. As they work together to make the project a success, can Rachel give up her lifelong goals without losing her identity as well?

Brunch at Bittersweet Café (The Saturday Night Supper Club, ,, 2019)
"From the RITA Award-winning author of Five Days in Skye comes a sweet, romantic treat that will leave you hungry for more. Baker and pastry chef Melody Johansson has always believed in finding the positive in every situation, but seven years after she moved to Denver, she can't deny that she's stuck in a rut. One relationship after another has ended in disaster, and her classical French training is being wasted on her night job in a mediocre chain bakery. Then the charming and handsome private pilot Justin Keller lands on the doorstep of her workplace in a snowstorm, and Melody feels like it's a sign that her luck is finally turning around. Justin is intrigued by the lively bohemian baker, but the last thing he's looking for is a relationship. His own romantic failures have proven that the demands of his job are incompatible with meaningful connections, and he's already pledged his life savings to a new business venture across the country--an island air charter in Florida with his sister and brother-in-law. Against their better judgment, Melody and Justin find themselves drawn together by their unconventional career choices and shared love of adventure. But when an unexpected windfall provides Melody with the chance to open her dream bakery-café in Denver with her best friend, chef Rachel Bishop, she's faced with an impossible choice: stay and put down roots with the people and place she's come to call home . . . or give it all up for the man she loves" --